2009
DOI: 10.1111/j.1468-232x.2009.00561.x
|View full text |Cite
|
Sign up to set email alerts
|

Product Market Competition and Human Resource Practices in the Retail Food Sector

Abstract: In the wake of Wal‐Mart and other mass merchandisers’ entry into food retailing, the nature of competition in the industry has changed radically. Using longitudinal data on workers and firms to construct measures of compensation and churning for traditional food retailers, this paper examines how these measures change in response to mass merchandiser entry. While there is considerable heterogeneity across retail food establishments, human resource practices are persistent even in the face of new external compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…The results, in conjunction with the work of Davis et al. (), suggest that the declining union coverage in food retailing is largely the result of unionized firms dropping out than firms dropping their union status.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…The results, in conjunction with the work of Davis et al. (), suggest that the declining union coverage in food retailing is largely the result of unionized firms dropping out than firms dropping their union status.…”
Section: Discussionsupporting
confidence: 56%
“…Recall that Davis et al. () demonstrated that heterogeneous competition was more likely to induce exit from the market than store‐level reductions in human resource practices. Hence the coefficient on UnionSupershare and the marginal effect may be reflecting the superior performance of those stores that successfully compete with supercenters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased competition from alternative retail formats brings significant changes into the retail food industry. Motivated by recognizing the changes, Davis et al [26] examine the labor market adjustment of firms in response to competitive entry by using a large-scale longitudinal employer-employee matched data set. By applying the analytic hierarchy process (AHP), Erol et al [27] propose indicators for future evaluation of industrial sustainability performance for grocery retailing in terms of the social, environmental and economic sustainability aspects.…”
Section: Related Workmentioning
confidence: 99%